REMOVAL OF AMMONIACAL NITROGEN FROM FISH PROCESSING WASTEWATER USING BIOAUGMENTATION TECHNIQUE - S.S. SARNAIK; V.V. PHALKE; P.P. KANEKAR (International Journal of Pharma and Bio Sciences, 2015)
Fish are a rich source of proteins beneficial to heart and eyes. Being perishable, they are processed immediately after collection. Water consumption in fish-processing industry is very large and high strength wastewaters rich in salts, ammoniacal nitrogen (NH3-N), organic load are generated which cannot be discharged without any treatment. The present investigation describes development of bioaugmentation process to reduce the concentration of NH3-N upto the drinking water level from the wastewater arising from an Up flow Anaerobic Sludge Blanket Reactor. Culture of Bacillus sp. was efficient in lowering the NH3-N content of the wastewater from initial 370 mg/L up to 4 mg/L within 5 days of incubation at ambient temperature (28±2 ºC). At bench scale level, the culture reduced the NH3-N content upto 60 mg/L from initial 558 mg/L. Thus, Bacillus sp. can be used successfully for developing a bioaugmentation process for removing NH3-N from wastewater generated in fish processing industry.